Distribution, abundance, diversity and habitat associations of fishes across a bioregion experiencing rapid coastal development. (5th September 2016) - McLean, Dianne L.; Langlois, Tim J.; Newman, Stephen J.; Holmes, Thomas H.; Birt, Matthew J.; Bornt, Katrina R.; Bond, Todd; Collins, Danielle L.; Evans, Scott N.; Travers, Michael J.; Wakefield, Corey B.; Babcock, Russ C.; et al.
Abstract: Knowledge of the factors that influence spatial patterns in fish abundance, distribution and diversity are essential for informing fisheries and conservation management. The present study was conducted in the nearshore Pilbara bioregion of north-western Australia where the dynamic marine environment is characterised by large embayments, numerous islands and islets, coexisting with globally significant petrochemical and mineral industries. Within Western Australia, this nearshore bioregion has high biodiversity and is considered to play an essential role in the recruitment of species of commercial importance. To better inform future investigations into both ecological processes and planning scenarios for management, a rapid assessment of the distribution, abundance and associations with nearshore habitats of fishes across the region was conducted. Baited remote underwater stereo-video systems (stereo-BRUVs) were used to simultaneously sample the fish assemblage and habitat composition. Generalised additive mixed models (GAMMs) were used to determine whether the abundance of fishes were related to habitat and a range of environmental variables (visibility, depth, distance to 30 m and 200 m depth isobars, boat ramps and the nearest large embayment (Exmouth Gulf). A diverse fish assemblage comprising 343 species from 58 families was recorded. The abundance and distribution patterns of fishery-target species and of the five most common and abundant species and families were linked positively with areas of high relief, hard coral cover, reef and macroalgae and negatively with the distance to the nearest oceanic waters (200 m depth isobar). This study provides information that can contribute to future marine spatial planning scenarios for management of the Pilbara using a unique, analytical approach that has broad application in biogeography. Highlights: Knowledge of factors driving fish abundance distribution is essential for management. A new method was used to simultaneously collect fish and habitat data from video. Fish-habitat relationships and distributions were studied along 340 km of coastline. High fish abundance and diversity were linked to areas of high conservation value.